A study to assess the pattern and determinants of road traffic injuries during a year, a tertiary care hospital-based study - Kumar, Manish; Niranjan, Anjana; Kumar, Sanjeev (International Journal of Research in Medical Sciences, 2017)
Background: Expansion in road network, motorization, and urbanization in the country has been accompanied by a rise in road accidents leading to road traffic injuries (RTIs). Today RTIs are one of the leading causes of deaths, disabilities, and hospitalizations with severe socioeconomic costs across the world. Methods: It is a retrospective record-based study of patient attending the causality of S.G.M.H. Rewa in Madhya Pradesh, India last one year, after road traffic accident. Study area was tertiary care hospital S.G.M.H. Rewa Madhya Pradesh, India. Simple random sampling method are used among all RTA victims visit to causality of S.G.M.H. Rewa. Study period was 1 year from st January 2015 to 3st December 2015. Sample size was 325 RTA and 412 victims. Main objective of the study was to determine sociodemographic factors and their circumstances leading to RTA, outcome and seasonal variations of RTA. Study variables were demographic, human, vehicular, environmental and time factors and statistical analysis, percentages, linear and logarithmic trend and chi-square. Results: 325 RTA was occurred in the year 2015 in which injured person were 412 who visited to causality of S.G.M.H Rewa in whom 298 (72.33%) were males and 114 (27.66%) were females, and most 49.02% of them belong to 21-40 year age. Alcohol consumption was found in 20.61% but fatality was high (76.11%) and high speed of the vehicle was the causing factor in 71.38% and case fatality was also high (73.94%) in high speed RTA. More number of RTA occurred at unfamiliar road ratio between RTA occurred at unfamiliar road and familiar road was 2.73:1 and fatality was also high in unfamiliar road accident. Conclusions: Most of the factors responsible for RTA and its fatal consequences are preventable. A comprehensive multipronged approach can mitigate most of them.